Aerobic Capacity Support for Anaerobic Alactasid Training (Speed Endurance) in Football: A Case Study of UPI Football UKM - Fathir, Ibnu Daffa Al; Rusdiana, Agus; Ugelta, Surdiniaty; Imanudin, Iman (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Football in Indonesia has a weakness, namely their physical condition is less able to survive for 90 minutes in the game. This is closely related to the player's endurance. When a football player has good VO2max endurance, it will be very easy to maintain his performance in playing, unlike when a player does not have good endurance, it will affect his game, fatigue causes a decrease in performance in the match. The purpose of this study was to determine whether there is aerobic capacity support for anaerobic alactasid training (speed endurance) in football. The method used in this study is descriptive quantitative. The sampling used in this study was non-probability with a purposive sampling technique. Twenty UPI Football UKM students took part as participants in this study. There are 2 types of tests carried out, namely; (1) Aerobic Capacity Testing (VO2Max) with the Balke test research instrument, (2) 30 m short-distance running training with a total of 10 x maximum repetitions with a predetermined rest time. The data obtained from the test results were then analyzed using SPSS software version 23, namely using the normality test and correlation test. From the results of data processing, the Sig value of the relationship between the VO2Max variable and the Speed ​​​​Endurance variable is 0.000, which means the Sig value <0.05 and the correlation value is 0.845. So it can be concluded that there is a very strong positive relationship between the VO2Max variable and Speed ​​​​Endurance.